Kelayakan dan Strategi Pengembangan Usaha Industri Kecil Tahu Di Kabupaten Kuningan, Jawa Barat - Nunung Nurhayati; Musa Hubeis; Sapta Raharja (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2012)
Kuningan District where agriculture is the inhabitant main livelihood, has the potential for agro based industry sectors. One of Small Industries (SI) which sustain to grow since the 1960's in the Kuningan District is Tofu industry. The purpose of this study were to analyze business performance, to analyze the needs and feasibility of business development and to formulate a strategy in business development of Tofu SI. Data collection methods used were field surveys and in-depth interviews with related experts. Information obtained from the District Government and KOPTI. Data processing technique was using Friedman test and the AHP. Feasibility analysis of business development  of tofu small industry obtained NPV of Rp395.696.655, IRR of 38,72%, B/C ratio of 3.10, PBP of 1.19 years and BEP value of 260.304 units. All these criteria show that further business development  is feasible. Tofu business development strategy based on AHP analysis covers aspects of product manufacturing processes, waste management and business financing. Priority strategies to improve the quality of products is by training human resources such as scheduling techniques relating in utilization of raw materials, raw material selection, division of work, techniques for preparing SOP and also supervision and quality control of products. Priority strategies for waste water treatment efforts is the training of waste water treatment into biogas, producing nata de soya and biofilter. While the priority strategies in the business financing is working capital loans from supplier cooperatives which is the KOPTI